A New Era for Trade?. (22nd January 2021) - Goldstein, Judith
Abstract : Trade policy decisions have direct, and almost immediate, effects on American jobs and wages. As result, historically, commercial policy has been highly partisan and closely associated with constituent demands. From this perspective, the post-World War II years were anomalous: trade policy was bipartisan and de-politicized. Due to rapid growth in the U.S. economy, those hurt by imports were easily re-employed, dampening the growth of a pro-protection coalition in either party. This facilitated a U.S.-led expansion of trade under the umbrella of commonly accepted international rules. In the last decades of the twentieth century, however, this pro-trade consensus began to unravel. While U.S. exports continued to thrive, the growth of regional and global value chains and the emergence of East Asian manufacturing giants caused job dislocation and a bifurcation of the U.S. economy around a skill premium. The Trump administration's response was to externalize these problems onto U.S. trading partners. The Biden administration needs a different strategy. Even though the Democratic party has been critical of aspects of the multilateral regime, Biden must re-connect with the international community. The United States should strive to be a better partner in the World Trade Organization (WTO), resist the capricious use of trade law, and rebuild a competitive domestic economy.